2016
DOI: 10.1002/adma.201504569
|View full text |Cite
|
Sign up to set email alerts
|

Crack‐Defined Electronic Nanogaps

Abstract: Achieving near-atomic-scale electronic nanogaps in a reliable and scalable manner will facilitate fundamental advances in molecular detection, plasmonics, and nanoelectronics. Here, a method is shown for realizing crack-defined nanogaps separating TiN electrodes, allowing parallel and scalable fabrication of arrays of sub-10 nm electronic nanogaps featuring individually defined gap widths.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
56
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 38 publications
2
56
0
Order By: Relevance
“…However, Si 3 N 4 is an insulator, hindering its application as electrodes in devices. Dubois et al reported crack‐defined electrodes with sub‐5 nm nanogaps in a thin electrically conductive film over a large area, obtained using TiN . However, TiN is brittle, and its conductivity is much lower than that of metal, limiting its application in electronic devices.…”
Section: Fabrication Methods For Sub‐5 Nm Nanogapsmentioning
confidence: 99%
“…However, Si 3 N 4 is an insulator, hindering its application as electrodes in devices. Dubois et al reported crack‐defined electrodes with sub‐5 nm nanogaps in a thin electrically conductive film over a large area, obtained using TiN . However, TiN is brittle, and its conductivity is much lower than that of metal, limiting its application in electronic devices.…”
Section: Fabrication Methods For Sub‐5 Nm Nanogapsmentioning
confidence: 99%
“…Successful fabrication of CJs requires precise control of the formation and propagation processes of the crack by utilizing well-designed stressconcentrating structures. While the realization of CJs has been demonstrated in initial experiments 2,21 , the impact of the different design parameters of CJs on the resulting cracks has not yet been thoroughly investigated. Specifically, we analyze theoretically and verify experimentally the influence of the dimensions and shape of the stress concentration structures (notches) in the electrode-bridge, the beam length of the electrode-bridge, and the anchor design of the electrode-bridge, on the formation and propagation of the crack.…”
Section: Introductionmentioning
confidence: 99%
“…A key advantage of the CJ methodology is that while the electrode-bridges are defined lithographically, the resulting crack-defined gaps are self-generated and have predictable atomic-scale dimensions that cannot be realized with conventional state-of-the-art nanofabrication technologies. CJs also display unique properties such as the possibility to realize high aspect ratios between gap-height and gap-width, and perfectly matching electrode surfaces 2 . Other works on the characterization of the mechanical properties of ductile and brittle thin films have also been reported using release of internal stress in suspended structures to generate various controlled stress loading situations [22][23][24] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations